Penggunaan Media Pembelajaran Bahasa Arab Berbasis Teknologi Informasi di Program Khusus Pengembangan Bahasa Arab (PKPBA) UIN Maulana Malik Ibrahim Malang - Abdul Muntaqim Al Anshory (Tarling : Journal of Language Education, 2020)
This study aims to determine the use of information technology-based Arabic learning media in the Arabic Language Center (PKPBA) UIN Maulana Malik Ibrahim Malang. This research is a descriptive quantitative study. The research subjects are lecturers of PKPBA UIN Maulana Malik Ibrahim Malang 2018-2019. The research instruments are observation and questionnaire. The data analysis technique used is descriptive statistical data analysis. The results shows that: 1) most lecturers (90%) have used information technology-based learning media in Arabic learning, 2) information technology-based learning media used are diverse, the most used are LCD projector and social media such as WhatsApp, Youtube, and Instagram, and 4) there are many obstacles faced by lecturers when using information technology-based learning media, namely learning media cannot be used for all lessons, media used is not in accordance with the time span of the lesson, the internet connection is low, the electrical power is accidentally shut down, the campus facilities does not support, and the lecturers are unskillfull in using media.